Interpreting Ruh as An Ecological Spirituality in Relation to Islam and Java Mysticism - Ubaidillah, Ubaidillah (UIN Maulana Malik Ibrahim Malang, 2021)
This research aims to explain about the acculturation of Islam and Javanese wisdom in interpreting ruh (spirit) as an ecological behavior in dealing with natural disaster and exploitative activities. The concept of spirit refers to the awareness to interpret the relationship between human and nature as a living macrocosm unit. The awareness, in Islam, is a dimension of Sufi that blends with nature, such as Javanese philosophy on the principle of the unity of nature. It employs descriptive analytical method by integrating theo-sufistic paradigm to find a turning point in the common ground between Islam and Java in preserving the nature. The analysis goes into three conclusions: 1) the concept of spirit in Islam is a representation of one’s love with nature as the manifestation of love with God in its essence; 2) Javanese beliefs and rituals in ruh as a living and valuable existence signified in mystical mythology for being haunted and sacred serves as theo-sufistic expressions of Islam and Java; 3) spirituality of the spirit generates awareness of the philosophy of Sangkan Paraning Dumadi, to live in harmony and balance between humans and nature. Penelitian ini ingin menjelaskan tentang akulturasi Islam dan kearifan Jawa dalam memaknai ruh sebagai perilaku ekologis dalam menangani kerusakan alam dan aktivitas eksploitatif. Konsep ruh yang dimaksud adalah kesadaran memaknai hubungan manusia dan alam sebagai satu kesatuan makrokosmos yang hidup. Kesadaran tersebut dalam Islam merupakan dimensi sufistik yang menyatu dengan alam sebagaimana falsafah Jawa tentang prinsip kesatuan alam. Penelitian ini menggunakan metode deskriptif analitis dengan pendekatan integratif dalam paradigma teo-sufistik untuk menemukan titik balik persamaan persepsi antara Islam dan Jawa dalam memelihara alam hayati. Hasilnya, pertama, konsep ruh dalam Islam adalah representasi dari mencintai alam sebagai manfestasi mencintai Tuhan dengan dzatnya. Kedua, keyakinan dan ritual yang dilakukan masyarakat Jawa atas ruh sebagai eksistensi yang hidup dan memberi manfaat yang mewujud dalam mitologis mistik yang disebut angker dan sakral sebagai ekspresi teo-sufistik Islam dan Jawa. Ketiga, spiritualitas ruh memberikan kesadaran dalam filosofi Jawa tentang Sangkan Paraning Dumadi sebagai makna hidup untuk dapat serasi dan seimbang antara manusia dan alam.